2020
DOI: 10.1016/j.neuint.2019.104647
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-guanylhydrazone hydrochloride mitigates long-term cognitive impairment in a neonatal sepsis model with involvement of MAPK and NFκB pathways

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…The mechanism of compound 65 was connected to a decreased pro-inflammatory cytokine release and COX-2 expression, as well as the suppression of microglia activation. Additionally, septic mice treated with derivative 65 did not exhibit the cognitive impairment and the anxiety behavior caused by LPS [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of compound 65 was connected to a decreased pro-inflammatory cytokine release and COX-2 expression, as well as the suppression of microglia activation. Additionally, septic mice treated with derivative 65 did not exhibit the cognitive impairment and the anxiety behavior caused by LPS [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aminoguanidine derivative indole-3-guanylhydrazone hydrochloride (LQM01) has been shown to have anti-inflammatory, antihypertensive, and antioxidant properties. Anxiety-like behavior and cognitive impairment induced by LPS in adult mice were reduced via LQM01 exposure during the neonatal period, which also attenuated inflammatory reactions and oxidative damage through the MAPK and NF-κB signaling pathways and microglial activation suppression [74]. Overall, these signaling pathways are critical in the progression of microglial activation through SAE, and a potential anti-SAE treatment target is blocking the above signaling pathways.…”
Section: Signaling Pathway Inhibitorsmentioning
confidence: 97%
“…Preclinical studies have revealed the ability of certain guanylhydrazone derivatives to control pain and inflammation in different experimental models in vivo [19,45]. Carrageenan-induced pleurisy was performed to evaluate the anti-inflammatory potential of LQM10.…”
Section: Effects Of Lqm10 On Carrageenaninduced Pleurisymentioning
confidence: 99%